(untitled) (IJOVTECH, 2026)
The confidence of the citizens in the government structures is still a fundamental pillar of good governance, especially in a third world setting such as that of Nigeria, where the historical aspects of centralized government have been a primary fault when it comes to losing the confidence of the citizens. This paper focuses on how community-based participatory governance has helped to enhance public trust in the state of Ebonyi, Nigeria, whose population mostly represents rural populations and whose service delivery has continued to be a disastrous problem in the area. The study has been based on a mixed-methodology approach, thus combining both primary (surveyor and interview) data of 450 respondents in 13 local government districts and secondary (literature) data covering classical theories of social capital to modern evaluations of African policy. Calculated results find that participatory processes including community assemblies and stakeholder consultations have a significant correlation with increased trust levels, with 68% of the respondents indicating that they felt more responsive of the government when they engaged in the decision making processes. The demographics analysis reveals that there is a high advocacy of inclusive governance among rural inhabitants (72percent of sample) and 35-54 years individuals (45percent of sample). Some obstacles, however, such as poor funding, elites, and illiteracy impede complete implementation. The analysis experts in the study is theoretically based on the works of Putnam on the social capital framework and the works of Fukuyama on the trust paradigm. The research highlights participatory governance as the conduit between the powers of the state and the agency of groups. It is suggested in the form of policy recommendations that community forums and capacity-building programs should become institutionalized to continue the process of trust-building. The research adds to the discussion of public administration because it draws attention to context-related methods of improving the level of democratic legitimacy in sub-Saharan Africa, as it can provide insights to policymakers who are eager to reduce the shortage of governance under the pressure of increasing accountability expectations.